The impact of carbon emission trading scheme on export: Firm-level evidence from China - Yang, Shubo; Shen, Qiangqiang; Jahanger, Atif; Ye, Penghao; Zhang, Huafeng; Balsalobre-Lorente, Daniel (Frontiers in Environmental Science, 2022)
The carbon emission trading scheme (ETS) is an important measure to implement China’s “double carbon” strategy.We use “China’s carbon emission trading pilot policy” as a quasi-natural experiment to identify theeffect of this market-based environmental regulation on a firm’s export and its impacting mechanisms.Based on the Propensity score matching and difference-in-differences (PSM-DID) method, we observe robust evidence that the carbon emissions trading pilot policy significantly increases the export of regulated firms. And also find that this policy positivelyaffects the exports of both SOEs and non-SOEs. Considering enterprise heterogeneity, the policy positivelyimpacts the exports of FDI firms, large firms, and low industrial concentrations. Moreover, we examine how environmental regulation could affect firmexport through technological innovation, productivity, and product research. The observable evidence leads us to cautiously conclude thatmarket-based environmental regulations in even developing countries could achieve export growth.Based on our findings, we suggest that: 1) policymakers should limit CO2 emissions quotas to ensure an appropriate increase in the price of CO2 emissions; 2) to design a unified carbon ETS market, researchers should explore ways to activate market-oriented environmental regulation tools based on the carbon emission price.